Exploiting the role of O6-methylguanine-DNA-methyltransferase (MGMT) in cancer therapy. - Sabharwal, A; Middleton, MR (2006)
Improving the efficacy of standard chemotherapy by targeting DNA repair mechanisms remains an important area of research. O6-methylguanine-DNA-methyltransferase (MGMT), which repairs alkylating agent damage, is one such target. Downregulation of the gene through epigenetic silencing has been shown to predict response to alkylating agent therapy in selected malignancies. Platinums have also been found to downregulate MGMT expression and this approach is currently under exploration. Another way to deplete O6-alkylguanine DNA alkyltransferase (AGT) levels is to modify methylating agent scheduling. Extended dosing has met with early favourable results. However, pseudosubstrates used to inhibit AGT activity have had limited success because of dose-limiting myelotoxicity. Topoisomerase I is 'trapped' on DNA by alteration of ligation kinetics following alkylating agent damage, leading to interest in combining AGT inhibitors or O6-alkylating agents with topoisomerase I inhibitors. DNA repair by AGT is an interesting target for cancer therapy that remains to be fully evaluated. The best results are likely to be achieved where its inhibition is part of treatment targeting multiple DNA damage processing pathways.